Impact of the COVID-19 Pandemic on Learning: Assessing Cognitive, Affective, and Psychomotor Skills - Kabir, S M Akramul; Abdullah , Mohamamd Nayeem; Tooheen , Rahat Bari; Hasan , Sayeed (Society & Sustainability, 2023)
The acquisition of cognitive, affective, and psychomotor skills is highly important for successful learning outcomes. This article aims to evaluate the Three-Domain Model (TDM) of learning (cognitive, affective, and psychomotor) during the COVID-19 online classes for tertiary students in Bangladesh. This current study aims at the psychometric evaluation and validation of tertiary students' learning loss during the pandemic. A survey questionnaire is administered using the Likert scale. The components of the questionnaire are based on the Three-Domain Model reflecting the cognitive, affective, and psychomotor skills of the students. The article informs of the learning loss due to the pandemic while suggesting the benefits of online classes. The major finding of the article is that learners lost their skills mainly related to the cognitive domain during the pandemic due to online classes. However, at the same time, their skills related to affective and psychomotor domains increased. Therefore, recommendations for minimizing learning loss are also provided to guide future empirical work in the post-pandemic era.